Financial Performance Analysis of Districts/Cities in North Maluku Province: Insights and Priorities - Noviena, Maria Sri; Sirat, Abdul Hadi; Hadady, Hartati (Jurnal Manajemen Bisnis, 2023)
This study seeks to examine the financial performance of Districts/Cities in North Maluku Province through descriptive analysis of financial ratios. The descriptive analysis method was chosen to depict and examine the financial conditions of the regions in detail based on available data. The findings reveal several key points: Firstly, the effectiveness ratio of Districts/Cities in North Maluku Province indicates ineffective performance, as the actual Local Own-Source Revenue (PAD) falls short of the set targets or budgets. Secondly, the fiscal decentralization ratio of Districts/Cities shows limitations in the regions' ability to finance local expenditures from PAD, with a very low level of financial independence. Thirdly, although the growth ratio of Districts/Cities shows positive fluctuations from 2018 to 2022, the growth remains low and unstable from one period to the next. Finally, there is a significant disparity between operational expenditure and capital expenditure, highlighting the need for prioritized budget allocations to support infrastructure development and overall community welfare. These research findings provide an in-depth perspective on the challenges and potential improvements in financial management at the local government level in North Maluku Province.